Essentials of financial risk management - Karen A. Horcher (Wiley, 2023)
A concise introduction to financial risk management strategies, policies, and techniques This ideal guide for business professionals focuses on strategic and management issues associated with financial risk. Essentials of Financial Risk Management identifies risk-mitigation policies and strategies; suggestions for determining an organization's risk tolerance; and sources of risk associated with currency exchange rates, interest rates, credit exposure, commodity prices, and other related events. Examples illustrate risk scenarios and offer tips on an array of management alternatives, including changes in the way business is conducted and hedging strategies involving derivatives.